Особливості інституалізації задунайських запорожців та дунайських козаків за матеріалами cфрагістики, вексилології та просторової локалізації - Бачинська, О. (Чорноморська минувшина, 2019)
Стаття присвячена особливостям процесів інституалізації у задунайців та дунайських козаків протягом останньої чверті XVIII – ХІХ ст. Запропоновано розглянути ці процеси за допомогою матеріалів сфрагістики, вексилології та просторової локалізації, зокрема печатки, бунчуки, прапори тощо. З’ясовано, що поява цих символів влади, по-перше, відображала легалізацію та вписування у відповідну державну систему певну козацьку інституцію – Січ або військо. По-друге, в кожній з цих інституцій на печатках і прапорах відбивались символи відповідної держави – Османської або Російської імперії, інколи з повагою до козацького минулого. Як, наприклад, поєднання ісламських і християнських символів на прапорах задунайців, або надання насеки (булави) дунайським козакам в Росії. The importance of symbols of power, such as seals, bunchuks or flags, can hardly be overestimated. Their appearance in one or another form testifies the legalization of a certain organization, institution, community. That is why the proposed article is devoted to the peculiarities of this process, of the process of institutionalization at the Transdanubian Cossacks and Danube Cossacks during the last quarter of XVIII – XIX centuries. It is suggested to consider this processes through materials of sphragistics, vexillology and spatial localization, such as seals, bunchuks, flags, etc. It was found that the emergence of these symbols of power first reflected the legalization and integration into a certain state system of the certain Cossack institution – Sich or the army. Secondly, in each of these institutions, the seals and flags displayed symbols of the corresponding state - the Ottoman or Russian Empire, sometimes with respect for the Cossack past. For example, it should be remembered combining the symbols of Islam with Christianity in the flags of the Transdanubian Cossacks, or providing the incisions (maces) to the Danube Cossacks in Russia. All these symbols kept for the Cossacks their traditions of life and respect to their glory. Важность символов власти, а именно: печати, полотнища или флаги, трудно переоценить. Их появление в той или иной форме свидетельствует о легализации определенной организации, учреждения, общества. Именно поэтому предложенная статья посвящена особенностям этого процесса, процесса институализации в задунайских запорожцев и дунайских казаков в последней четверти XVIII – XIX вв. Предложено рассмотреть эти процессы, используя материалы сфрагистики, вексиллологии и пространственную локализацию, в частности печати, полотнища, флаги и тому подобное. Установлено, что появление этих символов власти, во-первых, отражала легализацию и вписывания в определенную государственную систему соответствующую казацкую институцию – Сечь или войско. Во-вторых, в каждой из этих институций на печатях и знаменах отражались символы соответствующего государства - Османской или Российской империи, иногда с апеляцией к казацкому прошлому. Например, сочетание символов ислама с христианскими на флагах задунайцев, или предоставления насеки (булавы) дунайским казакам в России.